Pertumbuhan dan Hasil Beberapa Tanaman Palawija Akibat Sistem Tanam dan Pemupukan N, P, dan K pada Lahan Terkena Tsunami - Ainun Marliah (Jurnal Agrista, 2009)
Growth and Yield of Same Crop by Cropping System and Fertilization of N, P, K in in Tsunami Affected LandABSTRACT. The aim of study is know the effect of some cropping system and N, P, K fertilizer as well as the interaction of both factors to improve growth and yield maize, green bean, and groundnut. The experimental design was Completely Block Randomized Design with two factors and two replications. The first factor was cropping system: Those were maize monoculture, green bean monoculture, groundnut monoculture, maize-green bean intercropping, and maize-ground nut intercropping. Then the second factor was level of N, P, K fertilizer: Those were control, low dose (90 kg ha-1 N, 35 kg ha-1 P2O5, 20 kg ha-1 K2O) and high dose (180 kg ha-1 N, 70 kg ha-1 P2O5, 40 kg ha-1 K2O). The observation was done for growth and production of maize, green bean and ground nut. The research result showed that, cropping system did not have significant different on the height of maize plant at 15, 30, and 45 days after planting (DAP). Application of fertilizer had significant different on maize plant at 30 and 45 DAP and did not have significant different of maize plant at 15 DAP. Furthermore, cropping system and fertilizer application did not have significant different on the height of green bean and groundnut at 15 DAP, but cropping system and fertilizer application have very significant different on height of green bean and groundnut at 30 and 45 DAP, as well as interaction between cropping system and application fertilizer on height of green bean and groundnut at 30 and 45 DAP. Furthermore, cropping system did not have significant different on cornhusk-maize yield, and application of fertilizer have very significant different on cornhusk-maize yield. Cropping system and application of fertilizer have significant different on yield green bean and groundnut as well as interaction between cropping system and application of fertilizer on yield green bean and groundnut.